At Westonci.ca, we provide clear, reliable answers to all your questions. Join our vibrant community and get the solutions you need. Discover reliable solutions to your questions from a wide network of experts on our comprehensive Q&A platform. Discover detailed answers to your questions from a wide network of experts on our comprehensive Q&A platform.
Sagot :
Answer: 24c + 13
Step-by-step explanation:
f(x) = 6x + 1
(4c + 2)
f(4c + 2) = 6(4c + 2) + 1
f(4c + 2) = 24c + 13
Answer: f (4c + 2) = 24c + 13
Step-by-step explanation:
Given function
f(x) = 6x + 1
Function value that is asked to find
f (4c + 2)
Substitute values into the function
f (4c + 2) = 6 (4c + 2) + 1
Expand parentheses and apply the distributive property
f (4c + 2) = 6 · 4c + 6 · 2 + 1
f (4c + 2) = 24c + 12 + 1
Combine like terms
f (4c + 2) = 24c + (12 + 1)
f (4c + 2) = [tex]\boxed{24c+13}[/tex]
Hope this helps!! :)
Please let me know if you have any questions
We hope this information was helpful. Feel free to return anytime for more answers to your questions and concerns. We appreciate your time. Please revisit us for more reliable answers to any questions you may have. We're glad you chose Westonci.ca. Revisit us for updated answers from our knowledgeable team.